Hydrogen Sulphide (H2S) Awareness Training for Process 3 Services Solution Sdn Bhd - Abdul Aziz, Mohd Azoddein; Mazrul Nizam, Abu Seman; Wan Mohd Hafizuddin, Wan Yussof; Mariah, Che Mamat; Mohamad, Drani (2017)
Hydrogen Sulphide (H2S) is one of the major polluting substances found in petroleum refinery wastewater as well as other industrial and domestic sludge. Sulfide build up may cause several side effects like corrosion of concrete sewer pipes, releasing unpleasant odors, toxicity due to sulfide gas and negative effect to subsequent wastewater. Early detection and accurate quantification of hydrogen sulphide is necessary to assure equipment integrity, to comply with regulations and to ensure safety of workers. Routine maintenance and inspection activities become non-routine when hydrogen sulphide present in the workplace is above the Permissible Exposure Limit (PEL) 10 mg/L and become problematic when hydrogen sulphide concentrations are above the PEL level. Occupational Safety and Health Administrations (OSHA) enforceable ceiling limit for workplace exposure is set at 20 parts per million (ppm). The National Institute of Occupational Safety & Health (NIOSH) Permissible Exposure Limit (PEL) for hydrogen sulphide is set at 15 mg/m3 (10 ppm) averaged over a 10 minute period, and that work areas in which the concentration of hydrogen sulfide exceeds 70 mg/m3 be evacuated . P3SS Sdn. Bhd. is one of the petrochemical based industries which facing direct hydrogen sulphide exposure in their jobs. The objective of this program is to conduct workshops as part of development process to generate a training methodology in hydrogen sulphide handling, hydrogen sulphide monitoring and hydrogen sulphide surveillance, to apply the knowledge of mercury awareness and proper personal protective equipment (PPE) used while handling hydrogen sulphide.